Measuring The Performance Of 'Train A Trainer' Programme : A Case Study In Long Lamai, Sarawak, Malaysia - Sarah Flora, Samson Juan; Suriati Khartini, Jali; Edwin, Mit; John, Phoa (2010)
Long Lamai is a remote rural community, located close to the border between Indonesian Kalimantan and Sarawak in Malaysia. The Penan community has a population of approximately 500 people and they are mostly farmers. They have very limited interconnections with the outside world due to the distance between urban area and their village. Centre of Excellence in Rural Informatics (CoERI) from Universiti Malaysia Sarawak has successfully built a Telecentre which provides facilities of telephone, fax, internet, printing, and photocopying for the local community. Researchers of CoERI could only conduct basic computer trainings for them once in two months due to the high cost of travelling and other commitments. An initiative to overcome this problem has been identified which is by introducing a ‘Train a Trainer’ programme to the community. The programme is intended to train the locals to become trainers to enable them to train their own community. The paper would discuss on the methods used to design and develop training modules, challenges faced during the implementation and results of the performance of the trainers in conducting their classes. Through this programme, training the locals could greatly help in reducing the costs; however the quality of the training conducted by the locals varies, depending on the modules. This paper also looks at measuring the effectiveness of the programme at Long Lamai, Sarawak, Malaysia.